Coldzyme® Mouth Spray reduces duration of upper respiratory tract infection symptoms in endurance athletes under free living conditions - Davison, G.; Perkins, E.; Jones, A. W.; Swart, G. M.; Jenkins, A. R.; Robinson, H.; Dargan, K. (European Journal of Sport Science, 2021)
Upper respiratory tract infection (URTI) can compromise athlete preparation and performance, so countermeasures are desirable. The aim of this study was to assess the effects of ColdZyme® Mouth Spray (ColdZyme) on self-reported upper respiratory tract infection in competitive endurance athletes under free-living conditions. One hundred and twenty-three endurance-trained, competitive athletes (recruited across 4 sites in England, UK) were randomised to control (no treatment, n = 61) or ColdZyme (n = 62) for a 3-month study period (between December 2017 and March 2018; or December 2018 and April 2019). They recorded daily training and illness symptoms (Jackson common cold questionnaire) during the study period. A total of 130 illness episodes were reported during the study with no difference in incidence between groups (episodes per person: 1.1 ± 0.9 Control, 1.0 ± 0.8 ColdZyme, P = 0.290). Episode duration was significantly shorter in ColdZyme compared to Control: Control 10.4 ± 8.5 days vs. ColdZyme 7.7 ± 4.0 days, P = 0.016). Further analysis to compare episodes with poor vs. good compliance with ColdZyme instructions for use (IFU) within the ColdZyme group showed a greater reduction in duration of URTI when compliance was good (9.3 ± 4.5 days in ColdZyme poor IFU compliance vs. 6.9 ± 3.5 days in ColdZyme good IFU compliance, P = 0.040). ColdZyme may be an effective countermeasure to reduce URTI duration, which was significantly lower (by 26-34%) in the ColdZyme treatment group (with no influence on incidence). This may have implications for athlete performance.